Perlindungan Hukum Kreditur Dalam Pelaksanaan Eksekusi Hak Tanggungan - Elza Syarief; Yudhi Priyo Amboro; Risky Hadi Putra (Journal of Judicial Review, 2014)
The study aims to review and analyze the effectiveness of the application of the legislation – Act No. 4 of 1996 on the rights of the Legal Protection Against Creditors Dependents In Execution.The research method used was the normative research. The results showed the form of legal protection the certificate holder's rights of creditors against the debtor who did a dependent resistance time collateral was executed was a dependent Right certificate and certificate Rights over land.The occurrence of nonperforming loans or credit problems are generally caused by the global economic downturn are having an impact on inflation and the weakening of the business sector in addition to other factor was not assessed debtors character cooperative.